Diagnostic value of elevated CXCR4 and CXCL12 in neonatal sepsis. (February 2015) - Tunc, Turan; Cekmez, Ferhat; Cetinkaya, Merih; Kalayci, Tugce; Fidanci, Kursat; Saldir, Mehmet; Babacan, Oguzhan; Sari, Erkan; Erdem, Galip; Cayci, Tuncer; Kul, Mustafa; Kavuncuoglu, Sultan
Abstract Objective: Neonatal sepsis remains a major cause of morbidity and mortality in newborns. The chemokine CXCL12 and its receptor CXCR4 are now known to play an important role in inflammatory states. However, it is unclear how chemokines respond to late-onset neonatal sepsis. Methods: Patients were classified into the groups of septic and non-septic ones. Samples of venous blood were obtained from all septic and non-septic newborns at the beginning and within 48–72 h after initiation of treatment. Serum levels of CXCR4 and CXCL12 were measured. Results: Concentrations of IL-6, CXCR4 and CXCL12 at the time of diagnosis were significantly higher in the septic neonates compared with the non-septic ones. Additionally, there were statistically significant differences in septic neonates between the first and the second levels of IL-6, CXCR4, CXCL12 and I/T ratio. ROC curve analyses revealed that IL-6, CXCR4, CXCL12 and I/T ratio resulted in significant AUC with respect to early identification of septic neonates. Univariate logistic regression analysis showed that increased IL-6, CXCR4 and CXCL12 were strong predictors of neonatal LOS. Conclusions: Serum CXCR4 and CXCL12 levels increase in septic neonates and that both chemokines decrease within 48–72 h of treatment. Serum concentrations of both chemokines represent promising novel biomarkers for neonatal sepsis.